Em busca da origem das cores de 'O Livro de Como se Fazem as Cores': sobre as fontes de um receituário português medieval de materiais e técnicas de pintura - Cruz, António João (Cátedra de Estudos Sefarditas «Alberto Benveniste» da Universidade de Lisboa, 2010)
O Livro de Como se Fazem as Cores, that is, The Book on How to Make Colours, is a 15th century Portuguese compilation of receipts about painting materials and techniques for which sources and influences were searched. Contrary to the expectations, influences of the Mappae Clavicula were not found, but some similarities were detected between O Livro de Como se Fazem as Cores and Jehan Le Begue treatise’s Experimenta de Coloribus (1431), the H490 Montpellier Manuscript (1460-1480) and, to a lesser degree, thet Bolognese Manuscript also know as Segreti per Colori (first half of the 15i th century). These similarities manifested through the procedures on how to make some pigments, namely mosaic gold and silver blue, and through the names attributed to certain pigments or pigments’ raw materials.